2014
DOI: 10.1017/s1751731114000597
|View full text |Cite
|
Sign up to set email alerts
|

Herd monitoring to optimise fertility in the dairy cow: making the most of herd records, metabolic profiling and ultrasonography (research into practice)

Abstract: Fertility performance is intrinsically linked to the quality of the animal environment, overall management and nutrition. This review describes the use of dairy herd records, metabolic profiles and ultrasonographic findings at veterinary fertility examinations to monitor and manage dairy herd fertility. After calving, a cow has to overcome a series of physiological hurdles before establishing a pregnancy. The selection of timely key performance indicators (KPIs) that monitor specific events in the postpartum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
0
19
0
2
Order By: Relevance
“…This relationship could be attributed to the negative energy balance in high-yielding cows, and not to the urea level itself. Another explanation of this phenomenon could be the adaptability of the cows to high feed protein content, which translates into a reduction of the negative effect of high milk urea content on their fertility [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship could be attributed to the negative energy balance in high-yielding cows, and not to the urea level itself. Another explanation of this phenomenon could be the adaptability of the cows to high feed protein content, which translates into a reduction of the negative effect of high milk urea content on their fertility [7].…”
Section: Discussionmentioning
confidence: 99%
“…The results of performance recording and research findings [2,[5][6][7] show that fertility of (especially high-producing) cows is deteriorating. High-yielding cows show a higher ability to mobilize energy reserves during the early lactation period [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This relationship appears to be due to the negative energy balance observed in high-yielding cows, and not to the urea level itself. Another possible explanation of this phenomenon is the cows' adaptability to a high protein content in their feed, which translates into reducing the negative effect of high milk urea content on their fertility (17). Sawa et al (5) demonstrated that the urea level had a significant effect on the length of CI (417-434 days) in herds producing >6000 kg milk, with a particularly negative effect occurring at levels exceeding 300 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat breeding services recorded and compiled at the population level showed that 68.7% of returns to the oestrus occurred in 18 to 24 days period. Considering good oestrus detection, the target is set on 55% as described in [15]. Veterinary Medicine International [32].…”
mentioning
confidence: 99%